The Factors that Influenced the Obedience of Bacteriological Test toward Total coliform Content at Refill Drinking Water Depot in Kuantan Singingi District - Rosalina Helen Purwitasari; Zulkarnaini Zulkarnaini; Suyanto Suyanto (Program Pascasarjana Universitas Riau, 2017)
This Reseach was conducted in November 2016 until January 2017 located in Kuantan Singingi district. The purpose of this research is to analyze the effect of simultaneous and partial also the direct and indirect effect between the knowledge owner of refill drinking water depot, the cost of bacteriological test, the health worker supervision and physical environment of refill drinking water depot toward the obedience of bacteriological test, and analyzed the effect of obedience bacteriological test toward the Total coliform content. Based on the research was known that the knowledge variable, the cost, the supervision, physical environment had effected simultaneously and significant toward the obedience of bacteriological test. Partially there was no effect between the knowledge owner of refill drinking water depot toward the obedience of bacteriological test. While the variable of cost the bacterilogical test, the health worker supervision and physical environment had the significant effect toward the obedience of bacteriological test. The cost of bacteriological test was influenced directly toward the obedience of bacteriological test and inderectly through the variable of worker health supervision and physical environment. The supervision was influenced directly toward the obedience of bacteriological test and influenced indirectly through the cost variable and physical environment. The physical environment was influenced directly toward the obedience of bacteriological test and influenced indirectly through the cost variable and supervision. The obedience of bacteriological test has not significant effect toward Total Coliform contents at refill drinking water depot in Kuantan Singingi district.